Dulaglutide inhibits high glucose- induced endothelial dysfunction and NLRP3 inflammasome activation - Luo, Xiaojia; Hu, Yongmei; He, Sen; Ye, Qiran; Lv, Zhengbing; Liu, Jianxiong; Chen, Xiaoping (Archives of biochemistry and biophysics, 2019)
Activation of the NLRP3 inflammasome plays an important role in high glucose- induced endothelial dysfunction in patients with type 2 diabetes mellitus (T2DM). Dulaglutide, a newly developed glucagon-like peptide-1 receptor (GLP-1R) agonist, has been approved for the management of T2DM. In the current study, we aimed to investigate whether dulaglutide possesses a protective effect against high glucose- induced activation of the NLRP3 inflammasome. Our results indicate that dulaglutide treatment prevented high glucose- induced generation of reactive oxygen species (ROS) and protein carbonyl, as well as the expression of NADPH oxidase 4 (NOX-4) in human umbilical vein endothelial cells (HUVECs). Dulaglutide treatment could inhibit high glucose- induced release of lactate dehydrogenase (LDH) and the expression of TXNIP. Dulaglutide suppressed high glucose- induced activation of NLRP3 inflammasome by reducing the expression of NLRP3, ASC, and cleaved caspase 1 (P10). Notably, dulaglutide treatment suppressed high glucose- induced maturation of IL-1β and IL-18. Mechanistically, our findings indicate that SIRT1 was involved in this process by showing that knockdown of SIRT1 by transfection with SIRT1 siRNA abolished the inhibitory effects of dulaglutide on IL-1β and IL-18 secretion via suppression of NLRP3, ASC, and p10. These data suggest that dulaglutide might serve as a potential drug for the treatment of cardiovascular complications in T2DM patients.